Cliotide U1, a Novel Antimicrobial Peptide Isolated From Leaves - Mahnaz Nasre Taheri; Sima Sadat Seyedjavadi; Mehdi Goudarzi; Gholamhossein Ebrahimipour; Ali Hashemi (Bioinformatics and Biology Insights)
Aims: Antibiotic resistance is currently a major challenge to scientists. Thus, attempts have been made to develop new compounds with antimicrobial activity. In this research, a new antimicrobial peptide with antibacterial activity was isolated from the plant Urtica dioica . Methods: A new antimicrobial peptide, named cliotide U1, was purified through precipitation with ammonium sulfate and reverse-phase high-performance liquid chromatography. In silico methods analyzed the physicochemical properties of cliotide U1. The properties of the peptide, including antibacterial activity, pH stability, heat stability, cytotoxicity, and hemolytic activity, were also examined. Findings: The purified peptide was composed of 35 amino acids with a hydrophobicity ratio of 63% and a net charge of + 5. The antibacterial activity of cliotide U1 was observed against gram-negative and gram-positive bacteria with a minimum inhibitory concentration (MIC) of 1 to 4 µM. Cliotide U1 had less than 2% cytotoxic activity at the MIC range against the human embryonic kidney cell line 293 with no clear hemolytic activity. The stability of cliotide U1 was preserved at various temperatures (10-60°C) and pH (6-9). Conclusion: Our results demonstrated that cliotide U1 had potent antibacterial potential against gram-negative and gram-positive bacteria. Considering its properties, cliotide U1 can be introduced as a novel antibacterial candidate for expanding new therapeutic drugs.